2018
DOI: 10.3892/ol.2018.8441
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‑β decreases side population cells in hepatocellular carcinoma in�vitro

Abstract: Abstract. Hepatocellular carcinoma (HCC) can result from hepatitis B or C infection, fibrosis or cirrhosis. Transforming growth factor-β (TGF-β) is one of the main growth factors associated with fibrosis or cirrhosis progression in the liver, but its role is controversial in hepatocarcinogenesis. In the present study, the effect of TGF-β on the HCC Huh-7 and Huh-Bat cell lines was evaluated. To study the effect of TGF-β, Huh-7 and Huh-Bat cells were treated with TGF-β and a TGF-β receptor inhibitor (SB431542).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…In primary lung cancer cells, TGF-β exposure led to an increase in cancer stem cell population through repression of miRNA138 [ 113 ] while in colon cancer, TGF-β seems to play a key role in angiogenesis, tumor growth and metastasis [ 114 ]. On the other hand, in the context of hepatocellular carcinoma, TGF-β resulted in a decrease in cell survival of stem-like side populations [ 115 ]. Collectively, these studies highlight the importance of HIFs and TGF-β in the regulation of EMT, and provide support for the development of strategies exploiting these pathways to overcome therapy resistance.…”
Section: Emt At the Crossroad Of Stemnessmentioning
confidence: 99%
“…In primary lung cancer cells, TGF-β exposure led to an increase in cancer stem cell population through repression of miRNA138 [ 113 ] while in colon cancer, TGF-β seems to play a key role in angiogenesis, tumor growth and metastasis [ 114 ]. On the other hand, in the context of hepatocellular carcinoma, TGF-β resulted in a decrease in cell survival of stem-like side populations [ 115 ]. Collectively, these studies highlight the importance of HIFs and TGF-β in the regulation of EMT, and provide support for the development of strategies exploiting these pathways to overcome therapy resistance.…”
Section: Emt At the Crossroad Of Stemnessmentioning
confidence: 99%
“…These effects are reversed by the treatment with Galunisertib. Another work reported that the expression of CD133 and Vimentin was upregulated by treatment with the TGF-β receptor antagonist SB431542 [23]. Additionally, it was observed by Rani and colleagues that treatment with Galunisertib in vitro modulates the expression of stemness-related genes in invasive HCC cells (HLE and HLF) reducing the expression of CD44 and THY1 and consequently results in decrease in colony formation, liver spheroids and invasive growth capacity in vitro and in ex vivo human HCC samples [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies have reported that ANXA3 activated the JNK signaling pathway of stress-activated proteins in hepatocellular carcinoma (22–24). Furthermore, previous studies have demonstrated that the JNK signaling pathway activated CD133 + glioblastoma stem cell self-renewal to promote hepatocellular carcinoma differentiation (2527). The JNK signaling pathway plays a significant role in ANXA3-mediated cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%